Using the Google Earth Win Software in Teaching the “World Economic-Social Geography” Course - Artikova Gulnoza Eshmukhammadovna (International Journal on Integrated Education, 2022)
The Google Earth Win application is critical for working with maps, and this article discusses how to organize the "World Economic and Social Geography" lesson offered in the 9th grade of general secondary schools.